2017
DOI: 10.1017/s0007114517001106
|View full text |Cite
|
Sign up to set email alerts
|

Heat-stabilised rice bran consumption by colorectal cancer survivors modulates stool metabolite profiles and metabolic networks: a randomised controlled trial

Abstract: Rice bran (RB) consumption has been shown to reduce colorectal cancer (CRC) growth in mice and modify the human stool microbiome. Changes in host and microbial metabolism induced by RB consumption was hypothesised to modulate the stool metabolite profile in favour of promoting gut health and inhibiting CRC growth. The objective was to integrate gut microbial metabolite profiles and identify metabolic pathway networks for CRC chemoprevention using non-targeted metabolomics. In all, nineteen CRC survivors partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 60 publications
2
47
0
Order By: Relevance
“…Rice bran variation in composition of bioactive molecules has functional relevance to rice breeders that seek to improve bran for human and animal health. The results of this study support the feasibility that numerous phytochemicals that have reported medicinal mechanisms of action can be improved in rice bran through breeding [13,14,95]. Rice bran, regardless of varietal differences, has a valuable 'core' metabolome as well as a variable set of metabolites that differ among cultivars, which can be developed as an affordable food ingredient for a diverse global population that remains challenged to meet basic nutritional security needs.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Rice bran variation in composition of bioactive molecules has functional relevance to rice breeders that seek to improve bran for human and animal health. The results of this study support the feasibility that numerous phytochemicals that have reported medicinal mechanisms of action can be improved in rice bran through breeding [13,14,95]. Rice bran, regardless of varietal differences, has a valuable 'core' metabolome as well as a variable set of metabolites that differ among cultivars, which can be developed as an affordable food ingredient for a diverse global population that remains challenged to meet basic nutritional security needs.…”
Section: Discussionsupporting
confidence: 69%
“…Polished white rice is the major product with rice milling yields of 65-70% and the by-products comprised of 20% rice husk and 8-12% rice bran [8]. Rice bran has a broad spectrum of health benefits [9][10][11][12], partially due to a diverse array of bioactive metabolites [13,14]. Rice bran bioactive components include, but are not limited to γ-oryzanol [15], tocopherols, tocotrienols [16], carotenoids [17], γ-aminobutyric acid [18], octacosanol [19], squalene [20], unsaturated fatty acids [21], phytosterols and phenolic compounds [22].…”
Section: Introductionmentioning
confidence: 99%
“…Power calculation for this pilot study was based on effect sizes reported in a previous rice bran dietary intervention metabolomics study ( 29 , 30 ). Two-way analysis of variance (ANOVA) and Welch’s two-sample t -tests were used to determine statistical significance between groups, and ANOVA with repeated measures was used to determine statistical significance within groups ( p ≤ 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…85 A heat-stabilized rice bran diet offers the benets of bacterial richness and diversity in the gut, helps with microbial metabolism, modulates stool metabolite proles, and contributes to chemoprevention in colorectal cancer survivors. [86][87][88] The function of rice bran in altering gut microbiota might contribute to the relief of adverse gastrointestinal effects in cancer patients during chemotherapy. A study that enrolled patients with cervical cancer indicated that the oral intake of hydrolyzed rice bran effectively attenuated the diarrheal side effects of chemotherapy.…”
Section: Clinical Trialsmentioning
confidence: 99%